A GUIDE TO IMPLEMENTATIONAL ASPECTS OF THE SPATIAL DOMAIN INTEGRAL EQUATION ANALYSIS OF MICROSTRIP ANTENNAS - Hildebrand, Louis T. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
In the analysis of microstrip radiating structures integral equation methods rate among the more accurate approaches. By far the most demanding part in the use of these methods is the actual numerical implementation. This paper presents a detailed illustrated description of the numerical implementation of a spatial domain mixed-potential integral equation analysis of microstrip radiating structures. [Vol. 10, No. 1 (1995), pp 40-51]